Fragile-to-strong glass transition in two-dimensional vortex liquids - I. Maccari; L. Benfatto; C. Castellani; J. Lorenzana; C. De Michele (Physical Review Research)
The fragile-to-strong glass transition is a fascinating phenomenon that still presents many theoretical and experimental challenges. A major one is how to tune the fragility of a glass-forming liquid. Here, we study a two-dimensional (2D) system composed of vortices in a superconducting film, which effectively behaves as a 2D glass-forming liquid. We show that the kinetic fragility in this system can be experimentally varied by tuning a single parameter: the external magnetic field H applied perpendicularly to the film. This conclusion is supported by the direct comparison between the analysis of experimental measurements in an amorphous MoGe superconducting film and Monte Carlo simulations in a disordered XY model, that captures the universality class of the two-step melting transition. We show that by increasing disorder strength, a fragile-to-strong transition is induced, in close similarity with the experimental findings in a magnetic field. Our numerical results shed light on the evolution of the dynamical heterogeneity from a fragile-to-strong glass, as due to the subtle interplay between caging effects arising from hexatic order and strong random pinning.